2018
DOI: 10.1051/ctv/20183302125
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profile and antioxidant potential of four table grape (Vitis vinifera) cultivars grown in Douro region, Portugal

Abstract: The aim of this work was to improve the knowledge about the potential of Douro region (North of Portugal) to produce table grapes of superior quality. Skin, pulp, and seeds of four table grapes ‘Alphonse Lavallée’, ‘Cardinal’, ‘Dona Maria’ and ‘Muscat Hamburgo’ produced in Dour region, collected at commercial maturity stage, were evaluated. Phenolic compounds, organic acids and sugars were determined in each cultivar and in the different parts of the grape by HPLC-DAD, while the antioxidant properties were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…The ones found are gallic acid, protocatechuic acid, catechin, epicatechin, procyanidin, epigallocatechin, resveratrol, chlorogenic acid, coumaric acid, caffeic acid, and rutin. Organic acids and sugars are also present in seeds, skin, and pulp, the major ones being tartaric, malic, and citric acids, glucose, and fructose [ 131 ].…”
Section: Natural Ingredients From Northeast Of Portugalmentioning
confidence: 99%
“…The ones found are gallic acid, protocatechuic acid, catechin, epicatechin, procyanidin, epigallocatechin, resveratrol, chlorogenic acid, coumaric acid, caffeic acid, and rutin. Organic acids and sugars are also present in seeds, skin, and pulp, the major ones being tartaric, malic, and citric acids, glucose, and fructose [ 131 ].…”
Section: Natural Ingredients From Northeast Of Portugalmentioning
confidence: 99%
“…Grapes and wines are an excellent source of phenolic compounds as has been reported by many researchers (Chen et al, 2022;Gouvinhas et al, 2018;Han et al, 2017;Hosu et al, 2014;Mota et al, 2018). This fact is a possible explanation of the French paradox, which refers to the fact that France is a country with low incidence of coronary heart disease and mortality, despite French people having a diet high in fat and being heavy smokers (Renaud, 1992).…”
Section: Introductionmentioning
confidence: 85%
“…Phenolic compounds of grape berries are the third most abundant group, after sugars and organic acids [3]. Other studies [3,34,35] also indicated that grape berries belonging to different cultivars contain mostly chlorogenic acid, rutin, quercetin, syringic acid, pcoumaric acid, and catechin. Phenolic compounds are well known to contribute not only to organoleptic quality as color, astringency, and bitterness, but also to health benefits of berries.…”
Section: Phenolic Compoundsmentioning
confidence: 98%